Pengaruh Kualitas Pelayanan, Sanksi Perpajakan, Dan Self Assessment System Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Jakarta Pulogadung Tahun 2022 - Melinda, Renny; Susanto, Imam (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to determine the effect of Service Quality, Tax Sanctions, and Self Assessment System on Individual Taxpayer Compliance at Primary Tax Office of Pulogadung, Jakarta in 2022. With a sample consisting of 145 respondents who were selected through a probability sampling technique, namely simple random sampling. A quantitive approach was used in this research, with a questionnaire as a research instrument. The result of this study indicate that the service quality has a positive and significant effect on taxpayer compliance with a value 30,3%. Tax sanctions has a positive and significant effect on taxpayer compliance with a value 22,8%. And the self assessment system has a positive and significant effect on taxpayer compliance with a value 49%. While the service quality, tax sanction, and self assessment system has a positive and significant effect on taxpayer compliance with a value 55% and the remaining 45% is influenced by other variables outside the research.